Digitalisasi Arsip Keagamaan Hindu: Pelestarian Warisan Budaya di Era Revolusi Industri 5.0 - Wayan Murjana (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
Hindu religious archives contain significant spiritual, historical, and cultural values, necessitating systematic and sustainable preservation efforts. However, various studies indicate that the digitization of Hindu religious archives remains limited to technical implementation, lacking a comprehensive description of standardization and implementation strategies. This study aims to examine the methods, implementation, and strategy for digitization Hindu religious archives as an effort to preserve cultural heritage in the era of the 4.0 Industrial Revolution. The method employed is a literature review, which involves examining relevant scientific articles from national and international journals, as well as proceedings, accessed through Google Scholar. The results show that the digitization of Hindu religious archives has been carried out through various technological approaches to recognise the script of Hindu religious documents. Additionally, there are stages of digitization that can be systematically adopted, including digitization projects, pre- digitization classification, digital conversion, and post- digitization. These findings emphasise that digitization is not merely a technical process, but a strategy for preserving knowledge by integrating humanistic values and technology.